Developing a POE2WE-Based Interactive Mobile Application to Support Physics Learning - Nana Nana; Jamil Ahmad (Jurnal Pendidikan MIPA, 2026)
Innovation in learning is an essential requirement, particularly in addressing the challenges of 21st-century education, which demand more effective, interactive, and student-centered learning processes. Fundamentally, innovation activities require strategies and skills to enhance students’ learning effectiveness across the cognitive, affective, and psychomotor domains. One approach to achieving this is to implement an appropriate learning model that aligns with the characteristics of the subject matter and learners’ needs. In this context, the POE2WE learning model (Prediction, Observation, Explanation, Elaboration, Write, and Evaluation) is a relevant alternative, as it promotes active student engagement and supports the development of scientific and reflective thinking skills. This study employed the McKenney development model, which consists of three main stages: Design, Development, and Formative Evaluation. In the design stage, a needs analysis was conducted, followed by the development of a learning structure and the preparation of instructional content integrated with the POE2WE syntax. The development stage focused on creating an Android-based physics learning application equipped with interactive features, learning materials, and evaluation components, aligned with the POE2WE model. Subsequently, the formative evaluation stage was conducted to assess the product's feasibility and practicality through expert validation and limited user trials. The research sample consisted of 124 respondents, including Physics Education students from Siliwangi University and Midwifery students from the Tasikmalaya Health Polytechnic. Data were analyzed using validity and practicality tests to determine the quality of the developed product. The results indicated that the application achieved a very high level of validity, with a POE2WE learning model validity score of 0.92 and a media validity score of 0.88. Furthermore, the practicality test yielded a score of 88.3%, which falls into the “very practical” category. Therefore, the developed Android-based physics learning application is considered highly valid and practical for use as an innovative learning medium to support the physics learning process. Keywords: android application, POE2WE, and learning media.